2022
DOI: 10.1021/acs.jpca.2c07949
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Parallel Heat Bath Configuration Interaction

Abstract: Heat-bath configuration interaction (HCI) is a deterministic method that approaches the full CI limit at greatly reduced computational cost. In this work, computational improvements to the HCI algorithm are introduced targeting speed, parallel efficiency, and memory requirements. The new implementation introduces a hash function to distribute determinants and takes advantage of MPI and OpenMP for parallelism allowing for a (22e,168o) active space to be studied, which explicitly includes 2.39 × 10 7 variational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…All Coulomb integrals will therefore be evaluated using the Resolution of the Identity (RI) approximation. [43][44][45] The orbitals and RDMs for the reference WFs come from the heat-bath configuration interaction (HBCI) procedure [46][47][48][49][50] using a tight threshold (10 −5 Ha) for accuracy of the variational wavefunction. For atoms and small molecules, the RDMs from this approach will be essentially FCI quality.…”
Section: Computational Detailsmentioning
confidence: 99%
“…All Coulomb integrals will therefore be evaluated using the Resolution of the Identity (RI) approximation. [43][44][45] The orbitals and RDMs for the reference WFs come from the heat-bath configuration interaction (HBCI) procedure [46][47][48][49][50] using a tight threshold (10 −5 Ha) for accuracy of the variational wavefunction. For atoms and small molecules, the RDMs from this approach will be essentially FCI quality.…”
Section: Computational Detailsmentioning
confidence: 99%
“…16 In their numerical tests using a fragment extracted from a protein, they found that the Holder inequality is preferable for pairs and the Cauchy-Schwarz inequality is preferable for quartets. Heatbath configuration interaction (HCI) methods are the focus of a paper by the Zimmerman group at the University of Michigan, 17 and they report on a series of algorithmic improvements that take advantage of distributed-and shared-memory parallelism to achieve highly scalable performance. Next, Melo, Pederson, and Peralta describe an implementation of the Fermi-Loẅdin orbital self-interaction correction (FLOSIC) method that is suitable for existing quantum chemistry programs.…”
Section: ■ New Algorithms In Quantum Chemistrymentioning
confidence: 99%
“…Extrapolations to the complete basis set limit have also been undertaken for small molecules and transition metals . The parallelization of the HCI algorithm has also been significantly improved allowing large active spaces ( n = 22, ϕ = 168) to be considered . In our initial implementation of a HCI-selection-like algorithm, we use the standard approach of SCI theories and generate the entire F -space, subjecting them to HCI selection criteria.…”
Section: Introductionmentioning
confidence: 99%